The YUCCA-Auxin-WOX11 Module Controls Crown Root Development in Rice - Zhang, Tao; Li, Ruonan; Xing, Jialing; Yan, Lang; Wang, Rongchen; Zhao, Yunde (Frontiers in Plant Science, 2018)
A well-developed root system in rice can ensure plants to efficiently absorb nutrients and water. Auxin is a key regulator for various aspect of root development, but the detailed molecular mechanism by which auxin controls crown root development in rice is not understood. Herein, we establish a YUC-Auxin-WOX11 module that plays a central role in regulating crown root initiation and growth in rice. We show that YUC overexpression causes massive proliferation of crown roots, a phenotype that is dependent on the presence of the transcription factor WOX11. On the other hand, we find that disruption of TAA1, which functions upstream of YUC genes, greatly reduces crown root development. Moreover, the crown rootless phenotype of taa1 mutants was rescued by overexpression of WOX11. We show that WOX11 expression is induced in OsYUC1 overexpression lines, but is repressed in the taa1 mutants. Our results indicate that auxin synthesized by the TAA/YUC pathway activates WOX11 transcription, which subsequently drives crown root initiation and development.